Synthesis method of high-capacity negative electrode material for lithium ion battery
By using nano-scale silicon oxide and alkali metal salt solution in lithium-ion batteries to generate metasilicates, combined with heat treatment and carbon coating technology, nano-SiO@ metasilicate-G/C composite materials were prepared, which solved the problem of volume expansion of silicon-based materials after lithium embedded, and significantly improved the cyclic performance and specific capacity of the electrode.
Patent Information
- Application Number
- CN202510279313.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-11
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-03-11
AI Technical Summary
In existing lithium-ion batteries, the volume of silicon-based materials expands severely after being embedded with lithium, resulting in material powdering, electrode structure failure and cycle performance degradation.
Nano-scale silicon oxide sub-oxide and alkali metal salt solution were used to react solid-liquid to form metasilicates. Combined with heat treatment and carbon coating technology, nano-SiO@ metasilicate-G/C composite materials were prepared.
By reducing the Li+ diffusion path and alleviating volume expansion, the cycling performance and specific capacity of the electrode are improved, reaching 1000mAh/g to 1400mAh/g, and the capacity attenuation is smaller after 50 weeks of cycle.
Smart Images

Figure CN119786586A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of lithium ion battery materials, and in particular relates to a method for synthesizing a high-capacity negative electrode material for a lithium ion battery. Background Art
[0002] Lithium-ion battery is a kind of rechargeable battery that relies on the movement of lithium ions between the positive and negative electrodes to achieve the purpose of charging and discharging. It is mainly composed of four parts: positive electrode, negative electrode, electrolyte, and diaphragm. At present, it is mainly used in new energy vehicles, electric motorcycles, solar photovoltaic and wind power generation energy storage systems, smart grid energy storage systems, hospital backup UPS, EPS power supply, security lighting, drones, laptops, mining safety equipment, digital products and other fields.
[0003] Commercial lithium-ion batteries mainly use graphite materials as negative electrode materials. The reversible specific capacity of carbon materials has reached 360mAh / g, but its theoretical specific capacity is only 372mAh / g, indicating that the development of traditional graphite negative electrode materials has reached its limit, but it is still difficult to meet the requirements of battery energy density for future new energy electric vehicles. In order to further improve the energy density of lithium-ion batteries, many high-specific-capacity negative electrode materials have become hot topics in related research. Silicon-based materials (Si, SiO, etc.) have become the focus and hot topic of lithium-ion battery research due to their abundant reserves, high theoretical specific capacity, low lithium insertion and extraction potential, and low price.
[0004] However, the development of Si and SiO faces huge challenges. The most fatal problem is their expansion after lithium insertion. The volume expansion rate of Si after complete lithium insertion is as high as 300%, which causes the material to pulverize and the electrode structure to be destroyed during the charge and discharge process, resulting in a significant decrease in cycle performance. SiO contains less active Si, and due to the silicon dioxide (SiO2) and silicon dioxide (SiO x ) will generate irreversible products such as lithium silicate and lithium oxide during the first lithium insertion process to relieve expansion stress, so SiO has a smaller volume change rate than Si. However, its volume change rate is still around 200%, which is much larger than the volume change rate of graphite electrode (~10%). And SiO electrode materials also need to solve the problems of poor conductivity and low first-cycle coulomb efficiency. Therefore, overcoming the shortcomings of silicon-based materials and preparing silicon-based composite materials with excellent performance has become an urgent task for the development of high-capacity power batteries. Summary of the invention
[0005] In view of this, the present invention aims to overcome the defects in the prior art and proposes a method for synthesizing a high-capacity negative electrode material for a lithium-ion battery.
[0006] To achieve the above object, the technical solution of the present invention is achieved as follows: A method for synthesizing a high-capacity negative electrode material for a lithium-ion battery comprises the following steps: S1: adding nano-sized silicon dioxide obtained by sand grinding micron-sized silicon dioxide and alkali metal salt into deionized water to fully dissolve, thereby preparing an alkali metal solution with a mass percentage of 1-5wt%; S2: adding nano-sized silicon dioxide into the alkali metal solution, stirring and mixing evenly, and then drying to obtain a raw material powder; S3: heating the raw material powder to 750°C-850°C in an inert gas atmosphere for heat treatment to obtain a composite material in which nano-scale crystalline Si of suitable size is embedded in SiO and coated with metasilicate (referred to as nano-Si / SiO@metasilicate, the same below); S4: Nano Si / SiO@metasilicate and artificial graphite are mixed, and carbon is coated by heat treatment with asphalt in an inert gas atmosphere to obtain a high-capacity negative electrode material for lithium-ion batteries (referred to as nano Si / SiO@metasilicate-G / C, the same below).
[0007] In some embodiments of the present invention, the molar ratio of nano-sized silicon dioxide to alkali metal salt in step S2 is (25-35):1.
[0008] In some embodiments of the present invention, the molar ratio of nano-sized silicon dioxide to alkali metal salt in step S2 is 30:1.
[0009] In some embodiments of the present invention, the heating temperature in step S3 is 800°C.
[0010] In some embodiments of the present invention, the Dv50 particle size of the nano-scale silicon dioxide in step S1 is 20-900 nm.
[0011] In some embodiments of the present invention, the alkali metal salt is one or a mixture of two or more of Li2CO3, Na2CO3, K2CO3.
[0012] In some embodiments of the present invention, the alkali metal salt is Li2CO3.
[0013] In some embodiments of the present invention, the heat treatment time in step S3 is 3 to 5 hours.
[0014] In some embodiments of the present invention, the heating time in step S3 is 4 hours.
[0015] In some embodiments of the present invention, the mass ratio of nano-Si / SiO@metasilicate, artificial graphite, and asphalt in step S4 is (1-10): (1-5): (1-10).
[0016] In some embodiments of the present invention, the inert gas is nitrogen or argon.
[0017] In some embodiments of the present invention, the rotation speed of the stirring process in step S2 is 300-600 revolutions per minute, and the stirring time is 12-24 hours.
[0018] Compared with the prior art, the present invention has the following advantages: (1) The present invention uses nano-SiO. Compared with commercially available micron-SiO, nano-SiO will bring shorter Li + The diffusion path and smaller expansion stress during lithium insertion are beneficial to improving the electrode cycle performance. Metasilicates generated by the uniform solid-liquid reaction of alkali metal salt solution and SiO can alleviate the volume expansion of nano-SiO materials during lithium insertion and provide Li + At the same time, the alkali metal cations in the alkali metal salt solution modify the SiO amorphous network structure, promote the disproportionation reaction of SiO (SiO→crystalline Si+SiO2), and control the amount of alkali metal salt added and the heat treatment temperature to adjust the crystalline Si in SiO to a suitable size (5~10nm). A crystalline Si of a suitable size is beneficial to inhibit the volume expansion of SiO during the charge and discharge cycle and improve the cycle performance of the electrode. The conductivity and cycle stability of the negative electrode material are improved by introducing graphite and carbon coating. After half-cell assembly, it was innovatively found to be a new type of high-capacity negative electrode material through electrochemical performance testing.
[0019] (2) The high-capacity negative electrode material prepared by the present invention has a specific capacity of 1000 mAh / g to 1400 mAh / g, and has a small capacity attenuation after 50 cycles. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The particle size distribution diagram of the commercial micron SiO used in Example 1, Dv50 = 5.73 μm; Figure 2 The particle size distribution diagram of nano-SiO obtained by grinding commercial micron-SiO sand in Example 1, Dv50=879nm; Figure 3 This is a SEM image of the commercial micron SiO used in Example 1; Figure 4 This is a SEM image of nano-SiO obtained after sand grinding in Example 1; Figure 5 The 50-cycle performance diagram of the negative electrode material made of commercial micron SiO and the negative electrode material made of nano-SiO obtained by sand grinding; Figure 650 cycle performance diagrams of negative electrode materials prepared by heating at 600°C, 700°C and 800°C for 4h in Comparative Examples 2 to 4 with a molar ratio of SiO:Li2CO3=16:1; Figure 7 50 cycle performance diagrams of negative electrode materials prepared by heating at 600°C, 700°C and 800°C for 4h in Comparative Examples 5 to 7 with a molar ratio of SiO:Li2CO3=20:1; Figure 8 50 cycle performance diagrams of negative electrode materials prepared by heating at 600° C., 700° C. and 800° C. for 4 h in Example 1, Comparative Example 8 and Comparative Example 9 with a molar ratio of SiO:Li2CO3=30:1; Fig. 9 XRD pattern of the negative electrode material prepared by heating at 800°C for 4h in Example 1 with a molar ratio of SiO:Li2CO3=30:1; Fig.10 XRD pattern of nano-SiO prepared by heating at 800°C for 4h in comparative example 1 with a molar ratio of SiO:Li2CO3=1:0; Fig.11 HRTEM image of nano-Si / SiO@Li2SiO3 prepared by heating at 800°C for 4h in comparative example 1 with a molar ratio of SiO:Li2CO3=1:0; Fig.12 HRTEM image of nano-Si / SiO@Li2SiO3 prepared by heating at 600°C for 4h in comparative example 8 with a molar ratio of SiO:Li2CO3=30:1 (the lattice spacing of the white circle in the figure is d=0.313nm, corresponding to crystalline Si); Fig.13 HRTEM image of nano-Si / SiO@Li2SiO3 prepared by heating at 700°C for 4h in comparative example 9 with a molar ratio of SiO:Li2CO3=30:1 (the lattice spacing of the white circle d=0.313nm corresponds to crystalline Si, and the lattice spacing of the yellow circle d=0.330nm corresponds to Li2SiO3 grains); Fig.14 HRTEM image of nano-Si / SiO@Li2SiO3 prepared by heating at 800°C for 4h in the molar ratio of SiO:Li2CO3=30:1 in Example 1 (the lattice spacing of the white circle d=0.313nm corresponds to crystalline Si, and the lattice spacing of the yellow circle d=0.330nm corresponds to Li2SiO3 grains); Fig.15HRTEM image of nano-Si / SiO@Li2SiO3 prepared by heating at 800°C for 4h in comparative example 5 with a molar ratio of SiO:Li2CO3=20:1 (the lattice spacing of the white circle in the figure is d=0.313nm, corresponding to crystalline Si); Fig.16 This is a SEM image of the negative electrode material prepared in Example 1; Fig.17 50 cycle performance diagrams of negative electrode materials prepared in Examples 1 to 5; Fig.18 This is a 50-cycle performance diagram of the negative electrode material prepared in Comparative Example 1; Fig.19 This is a 50-cycle performance diagram of the negative electrode material prepared in Comparative Example 2; Fig. 20 This is a 50-cycle performance diagram of the negative electrode material prepared in Comparative Example 3; Fig.21 This is a 50-cycle performance diagram of the negative electrode material prepared in Comparative Example 4; Fig. 22 This is a 50-cycle performance diagram of the negative electrode material prepared in Comparative Example 5; Fig.23 This is a 50-cycle performance diagram of the negative electrode material prepared in Comparative Example 6; Fig.24 This is a 50-cycle performance diagram of the negative electrode material prepared in Comparative Example 7; Fig.25 This is a 50-cycle performance diagram of the negative electrode material prepared in Comparative Example 8; Fig.26 This is a 50-cycle performance diagram of the negative electrode material prepared in Comparative Example 9. DETAILED DESCRIPTION
[0021] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be understood as limiting the present invention.
[0022] Unless otherwise defined herein, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs.
[0023] Where values are described herein as a range, it should be understood that such disclosure includes disclosure of all possible sub-ranges within that range, as well as specific values falling within that range, regardless of whether a specific value or a specific sub-range is explicitly stated.
[0024] In this document, "multiple" and the like, unless otherwise specified, refer to a number greater than 2 or equal to 2. For example, "one or more" means one or greater than or equal to two.
[0025] In this document, the terms “preferred” and “more preferred” are only used to describe implementation methods or examples with better effects, and it should be understood that they do not constitute limitations on the scope of protection of the present invention.
[0026] In this document, the words "further" and the like are used for descriptive purposes to indicate differences in content, but should not be construed as limiting the scope of protection of the present invention.
[0027] In this article, the term "and / or" is a description of the association relationship of objects, indicating that three relationships may exist. For example, A and / or B means: A or B, or A and B.
[0028] As used herein, the term "about" means + / - 10%, preferably + / - 5%, more preferably + / - 1% of the specified value.
[0029] The terms “include,” “including,” “have,” “contain,” etc. used in this article are open-ended terms, meaning including but not limited to.
[0030] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention pertains. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention.
[0031] The present invention will be described in detail below with reference to the embodiments.
[0032] Example 1
[0033] A method for synthesizing a high-capacity negative electrode material for a lithium-ion battery comprises the following steps: S1: Micron-sized silicon dioxide (purchased from Hunan Jinsi Technology Co., Ltd., product model KSP1, the same below) was sand-milled to obtain nano-sized silicon dioxide, and Li2CO3 was added into deionized water to fully dissolve, and an alkali metal solution with a mass percentage of 2wt% was prepared. The molar ratio of nano-SiO to Li2CO3 was 30:1; Figure 1 is the particle size distribution of commercial micron SiO before sand milling. Figure 2 The particle size distribution after sand milling is shown in Figure 2. By comparison, it can be seen that nano-SiO2 was successfully prepared by sand milling. Figure 3 and Figure 4 The SEM images of commercial SiO before and after grinding prove the successful preparation of nano-SiO.
[0034] S2: adding nano-SiO2 into the alkali metal solution and stirring to mix evenly, wherein the stirring speed is 450 revolutions per minute, the stirring time is 24 hours, and the mixed solution is dried to obtain a raw material powder; S3: Nano-Si / SiO@Li2SiO3 prepared by heat treatment at 800℃ for 4h in argon environment (its XRD pattern is shown in Fig. 9 shown); S4: Nano Si / SiO@Li2SiO3, artificial graphite and asphalt are carbonized and coated in an argon atmosphere at a mass ratio of 6:4:5 to obtain nano Si / SiO@metasilicate-G / C.
[0035] The SEM of nano-Si / SiO@metasilicate-G / C prepared in Example 1 is as follows: Fig.16 As shown in the figure, it can be seen that nano-Si / SiO@Li2SiO3 and graphite are uniformly mixed together, and the amorphous carbon formed by the pyrolysis of asphalt is well coated on the surface of the composite material. After testing, its electrochemical performance is as follows Fig.17 As shown, the first discharge capacity is 1281.8 mAh g -1 The first coulombic efficiency is 74.82%. After 50 cycles, the discharge capacity is 818.1 mAh g -1 .
[0036] Example 2
[0037] A method for synthesizing a high-capacity negative electrode material for a lithium-ion battery comprises the following steps: S1: Add nano-sized silicon dioxide obtained by sand grinding micron-sized silicon dioxide and Li2CO3 into deionized water to fully dissolve, and prepare an alkali metal solution with a mass percentage of 3wt%, wherein the molar ratio of nano-SiO to Li2CO3 is 25:1; S2: Add nano-SiO2 into the alkali metal solution and stir to mix evenly, wherein the stirring speed is 500 rpm and the stirring time is 18 hours. Dry the mixed solution to obtain raw material powder; S3: Nano-Si / SiO@Li2SiO3 prepared by heat treatment at 750℃ for 4h in an argon environment; S4: Nano Si / SiO@ Li2SiO3, artificial graphite and asphalt are carbonized and coated in an argon atmosphere at a mass ratio of 6:4:5 to obtain nano Si / SiO@ metasilicate-G / C.
[0038] After testing, the electrochemical performance of the nano-Si / SiO@metasilicate-G / C prepared in Example 2 is as follows: Fig.17 As shown, the first discharge capacity is 1277.1 mAh g -1The first coulombic efficiency is 74.32%. After 50 cycles, the discharge capacity is 706.6 mAh g -1 .
[0039] Example 3
[0040] A method for synthesizing a high-capacity negative electrode material for a lithium-ion battery comprises the following steps: S1: Add nano-sized silicon dioxide obtained by sand grinding micron-sized silicon dioxide and Li2CO3 into deionized water to fully dissolve, and prepare an alkali metal solution with a mass percentage of 4wt%, wherein the molar ratio of nano-SiO to Li2CO3 is 25:1; S2: Add nano-SiO2 into the alkali metal solution and stir to mix evenly, wherein the stirring speed is 450 rpm and the stirring time is 12h. Dry the mixed solution to obtain raw material powder; S3: Nano-Si / SiO@Li2SiO3 prepared by heat treatment at 850℃ for 4h in an argon environment; S4: Nano Si / SiO@ Li2SiO3, artificial graphite and asphalt are carbonized and coated in an argon atmosphere at a mass ratio of 6:4:5 to obtain nano Si / SiO@ metasilicate-G / C.
[0041] After testing, the electrochemical performance of the nano-Si / SiO@metasilicate-G / C prepared in Example 3 is as follows: Fig.17 As shown, the first discharge capacity is 1324.1 mAh g -1 The first coulombic efficiency is 72.88%, and after 50 cycles, the discharge capacity is 796 mAh g -1 .
[0042] Example 4
[0043] The difference between this embodiment and embodiment 1 is that the alkali metal salt solution is a Na2CO3 solution, and its mass percentage concentration is 1wt%. After testing, the electrochemical performance of the nano-Si / SiO@metasilicate-G / C prepared in embodiment 4 is as follows: Fig.17 As shown, the first discharge capacity is 1193 mAh g -1 The first coulombic efficiency is 76.82%. After 50 cycles, the discharge capacity is 749.6 mAhg -1 .
[0044] Example 5
[0045] The difference between this embodiment and embodiment 1 is that the alkali metal salt solution is a K2CO3 solution with a mass percentage concentration of 5wt%. After testing, the electrochemical performance of the nano-Si / SiO@metasilicate-G / C prepared in embodiment 5 is as follows: Fig.17As shown, the first discharge capacity is 1115.1 mAh g -1 The first coulombic efficiency is 74.43%. After 50 cycles, the discharge capacity is 738.9 mAh g -1 .
[0046] Comparative Example 1 The difference between this comparative example and Example 1 is that the molar ratio of nano-SiO to Li2CO3 in step S1 is SiO:Li2CO3=1:0, and the prepared nano-SiO (whose XRD pattern is shown in FIG. Fig.10 As shown in the figure), nano-SiO, artificial graphite and asphalt were carbonized in an argon atmosphere at a mass ratio of 6:4:5 to obtain nano-Si / SiO-G / C. The electrochemical performance of the nano-Si / SiO-G / C was tested as follows: Fig.18 As shown in FIG. 1 , it can be seen that the volume expansion of SiO during the lithium insertion and extraction process leads to a continuous decrease in capacity. The electrochemical performance of Comparative Example 1 is shown in FIG. Fig.18 As shown, the first discharge capacity is 1200.1 mAh g -1 The first coulombic efficiency is 75.32%. After 50 cycles, the discharge capacity is 465.3 mAh g -1 .
[0047] Comparative Example 2 The difference between this comparative example and Example 1 is that the molar ratio of nano-SiO to Li2CO3 in step S1 is SiO:Li2CO3=16:1. The electrochemical performance of the nano-Si / SiO@metasilicate-G / C negative electrode material prepared in Comparative Example 2 is as follows: Fig.19 As shown, the first discharge capacity is 146.6 mAh g -1 The first coulombic efficiency is 70.46%. After 50 cycles, the discharge capacity is 98.74 mAh g -1 .
[0048] Comparative Example 3 The difference between this comparative example and Example 1 is that the molar ratio of nano-SiO to Li2CO3 in step S1 is SiO:Li2CO3=16:1, and the heat treatment temperature in step S3 is 600°C. The electrochemical performance of the nano-Si / SiO@metasilicate-G / C negative electrode material prepared in comparative example 3 is as follows: Fig. 20 As shown, the first discharge capacity is 224.5 mAh g -1 The first coulombic efficiency is 76.5%, and after 50 cycles, the discharge capacity is 212.9 mAh g -1 .
[0049] Comparative Example 4 The difference between this comparative example and Example 1 is that the molar ratio of nano-SiO to Li2CO3 in step S1 is SiO:Li2CO3=16:1, and the heat treatment temperature in step S3 is 700°C. The electrochemical performance of the nano-Si / SiO@metasilicate-G / C negative electrode material prepared in comparative example 4 is as follows: Fig.21 As shown, the first discharge capacity is 226.8 mAh g -1 The first coulombic efficiency is 79.53%. After 50 cycles, the discharge capacity is 208.6 mAh g -1 .
[0050] Comparative Example 5 The difference between this comparative example and Example 1 is that the molar ratio of nano-SiO to Li2CO3 in step S1 is SiO:Li2CO3=20:1. The electrochemical performance of the nano-Si / SiO@metasilicate-G / C negative electrode material prepared in Comparative Example 5 is as follows: Fig. 22 As shown, the first discharge capacity is 1004.3 mAh g -1 The first coulombic efficiency is 78.11%. After 50 cycles, the discharge capacity is 607 mAh g -1 .
[0051] Comparative Example 6 The difference between this comparative example and Example 1 is that the molar ratio of nano-SiO to Li2CO3 in step S1 is SiO:Li2CO3=20:1, and the heat treatment temperature in step S3 is 600°C. The electrochemical performance of the nano-Si / SiO@metasilicate-G / C negative electrode material prepared in comparative example 6 is as follows: Fig.23 As shown, the first discharge capacity is 1315.8 mAh g -1 The first coulombic efficiency is 69.79%. After 50 cycles, the discharge capacity is 422.5 mAh g -1 .
[0052] Comparative Example 7 The difference between this comparative example and Example 1 is that the molar ratio of nano-SiO to Li2CO3 in step S1 is SiO:Li2CO3=20:1, and the heat treatment temperature in step S3 is 700°C. The electrochemical performance of the nano-Si / SiO@metasilicate-G / C negative electrode material prepared in comparative example 7 is as follows: Fig.24 As shown, the first discharge capacity is 1146 mAh g -1 The first coulombic efficiency is 77.93%. After 50 cycles, the discharge capacity is 470.1 mAh g -1 .
[0053] Comparative Example 8 The difference between this comparative example and Example 1 lies in that the heat treatment temperature in step S3 is 600 °C. After testing, the electrochemical performance of the nano-Si / SiO@metasilicate-G / C anode material prepared in Comparative Example 8 is as follows Fig.25 shown, the initial discharge specific capacity is 1149.4 mAh g -1 , the initial Coulombic efficiency is 75.14%, and after 50 cycles, its discharge specific capacity is 460.4 mAh g -1 .
[0054] Comparative Example 9 The difference between this comparative example and Example 1 lies in that the heat treatment temperature in step S3 is 700 °C. After testing, the electrochemical performance of the nano-Si / SiO@metasilicate-G / C anode material prepared in Comparative Example 9 is as follows Fig.26 shown, the initial discharge specific capacity is 1214 mAh g -1 , the initial Coulombic efficiency is 77.11%, and after 50 cycles, its discharge specific capacity is 476.6 mAh g -1 .
[0055] Figure 5 Figure 50 shows the cycling performance graphs of the anode materials directly prepared from the nano-SiO prepared in Example 1 and the anode materials directly prepared from commercially available micron-sized SiO. The initial discharge specific capacity of the anode materials directly prepared from commercially available micron-sized SiO is 2282.0 mAh g -1 , the initial Coulombic efficiency is 47.8%, and after 10 cycles, its discharge specific capacity is 33 mAh g -1 . It can be seen that the cycling performance of nano-SiO is improved compared to micron-SiO.
[0056] Figure 6-Figure 8 Figure 50 shows the cycling performance graphs of Si / SiO@Li2SiO3 prepared with different amounts of Li2CO3 incorporated and heat treatment temperatures. It can be seen that by controlling the amount of Li2CO3 incorporated and the heat treatment temperature, the structure of Si / SiO@Li2SiO3 can be controlled, thereby improving the cycling performance of the material. The structure of SiO is composed of amorphous Si surrounded by amorphous SiO2 and some low-valence silicon oxides SiO x (0 < X < 2). At high temperatures, SiO2 in SiO reacts with Li2CO3 (Li2CO3 + SiO2 → Li2SiO3 + CO2). At the same time, the presence of Li2CO3 promotes the disproportionation reaction of SiO (SiO → crystalline Si + SiO2). And the scale of crystalline Si can be controlled by controlling the amount of Li2CO3 incorporated and the heat treatment temperature. By Figure 11-Figure 15In the comparison of HRTEM images of nano-Si / SiO@Li2SiO3 prepared in different embodiments and comparative examples, it can be seen that the crystalline Si scales in different materials are different. The molar ratio with the best cycle performance is SiO:Li2CO3=30:1. The crystalline Si scale of nano-Si / SiO@Li2SiO3 prepared by heating at 800℃ for 4h should be the best (5-10nm).
[0057] Depend on Fig.17 and Fig.18 It can be seen that compared with the negative electrode material prepared in comparative example 1, the negative electrode material prepared in example 1 has extremely excellent cycle stability, and after 50 cycles, the capacity has a smaller attenuation.
[0058] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for synthesizing a high-capacity negative electrode material for a lithium-ion battery, characterized in that: The steps include: S1: adding nano-sized silicon dioxide obtained by sand grinding micron-sized silicon dioxide and alkali metal salt into deionized water to fully dissolve, thereby preparing an alkali metal solution with a mass percentage of 1-5wt%; S2: adding nano-sized silicon dioxide into the alkali metal solution, stirring and mixing evenly, and then drying to obtain a raw material powder; S3: heating the raw material powder to 750°C-850°C in an inert gas atmosphere for heat treatment to obtain nano-Si / SiO@ metasilicate; S4: Nano-Si / SiO@ metasilicate and artificial graphite are mixed, and carbon is coated by heat treatment with asphalt in an inert gas atmosphere to obtain a high-capacity negative electrode material for lithium-ion batteries.
2. The method for synthesizing a high-capacity negative electrode material for a lithium-ion battery according to claim 1, characterized in that: In step S2, the molar ratio of nano-sized silicon dioxide to alkali metal salt is (25-35):
1.
3. The method for synthesizing a high-capacity negative electrode material for a lithium-ion battery according to claim 1, characterized in that: The Dv50 particle size of the nano-scale silicon dioxide in step S1 is 20-900 nm.
4. The method for synthesizing a high-capacity negative electrode material for a lithium-ion battery according to claim 1, characterized in that: The alkali metal salt is one of Li2CO3, Na2CO3, K2CO3 or a mixture of two or more thereof.
5. The method for synthesizing a high-capacity negative electrode material for a lithium-ion battery according to claim 1, characterized in that: The heat treatment time in step S3 is 3 to 5 hours.
6. The method for synthesizing a high-capacity negative electrode material for a lithium-ion battery according to claim 1, characterized in that: In step S2, the molar ratio of nano-sized silicon dioxide to alkali metal salt is 30:
1.
7. The method for synthesizing a high-capacity negative electrode material for a lithium-ion battery according to claim 1, characterized in that: The heating temperature in step S3 is 800°C.
8. The method for synthesizing a high-capacity negative electrode material for a lithium-ion battery according to claim 1, characterized in that: The heating time in step S3 is 4 hours.
9. The method for synthesizing a high-capacity negative electrode material for a lithium-ion battery according to claim 1, characterized in that: In step S4, the mass ratio of nano-Si / SiO@ metasilicate, artificial graphite and asphalt is (1-10): (1-5): (1-10).
10. The method for synthesizing a high-capacity negative electrode material for a lithium-ion battery according to claim 1, characterized in that: The rotation speed of the stirring process in step S2 is 300-600 revolutions per minute, and the stirring time is 12-24 hours.
Citation Information
Patent Citations
Lithium ion battery silicon substrate lithium salt composite negative electrode material and preparation method and application thereof
CN102881870A
Silicon monoxide / silicon / lithium metasilicate composite negative electrode material and preparation method thereof
CN108269979A
Preparation method of lithium ion battery negative electrode SEI film, lithium ion battery negative electrode material and application of material
CN111362269A
Pre-lithiated silicon monoxide negative electrode material as well as preparation method and application thereof
CN112038598A
Silicon monoxide based composite negative electrode material, preparation method thereof and lithium ion battery
CN112661163A